1993
DOI: 10.1055/s-2006-956515
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of the Essential Oil fromEucalyptus maidenii

Abstract: Using the standard assay on irritant activity testing (4), the phorbol ester exhibited a highly irritant activity on the mouse ear (ID = 0.05 pg/ear). Since skin irritancy is an indication of possible tumor promotion, the use of this plant as a medicine should be discouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 1 publication
4
26
0
6
Order By: Relevance
“…Its MIC concentration of 950 ng/ml is almost nine times higher than that of Schinus molle. Moreover, the essential oil and ethanolic extract of Schinus molle have been previously reported to show antifungal activity (Ross et al, 1980;Dikshit et al, 1986;Gundidza, 1993;Quiroga et al, 2001), however, this is the first time it has been shown for the aqueous extract (decoction 30%).…”
Section: Resultsmentioning
confidence: 94%
“…Its MIC concentration of 950 ng/ml is almost nine times higher than that of Schinus molle. Moreover, the essential oil and ethanolic extract of Schinus molle have been previously reported to show antifungal activity (Ross et al, 1980;Dikshit et al, 1986;Gundidza, 1993;Quiroga et al, 2001), however, this is the first time it has been shown for the aqueous extract (decoction 30%).…”
Section: Resultsmentioning
confidence: 94%
“…Existem relatos sobre a atividade antifúngica (Dikshit et al, 1986), antimicrobiana (Gundidza, 1993), inseticida (Chantraine et al, 1998) e repelente (Wimalatne et al, 1996) de óleos essenciais de S. molle, assim como relatos da atividade antimicrobiana (Siddiqui et al, 1995) e fungistática (Siddiqui et al, 1996) de óleos essenciais de S. terebinthifolius.…”
Section: Schinus Terebinthifoliusunclassified
“…The essential oil of Hoslundia opposita exhibited antimicrobial activity (Gundidza et al, 1992). An ethanolic extract of leaves of Leonotis nepetifolia exhibited moderate activity against poliomyelitis virus and coxsackie B2 virus, while the fruit ethanolic extract exhibited strong and moderate activity against viruses Poliomyelitis and Semliki Forest L10 .…”
Section: Previous Biological and Phytochemical Reports Of Some Plantsmentioning
confidence: 99%